Diurnal Body Temperature and Rate of Passage of Loggers in Lions - Ted Friend; Giulia Corsini; Vincent Manero; Raffaella Cocco (Animals, 2020)
The documentation of diurnal patterns in body temperature in lions could be important because disruption of circadian patterns can be a useful measure of distress. This study quantified changes in body temperature of seven African lions (Panthera leo) at 5 min intervals during cold conditions from noon until the ingested body temperature loggers were expelled the next day. Thirteen loggers were fed to 11 lions during their daily noon feeding, while ambient temperatures were also recorded using six data loggers. The lions had continuous access to their dens and exercise pens during the day but were restricted to their heavily bedded dens that also contained a heat lamp from 23:00 until 08:00 the next day. Body temperatures averaged 37.95 ± 0.42 °C at 15:50, and 36.81 ± 0.17 °C at 06:50 the next day, 30 min before the first loggers passed from a lion, and were significantly different (t-test, t = 8.09, df = 6, p < 0.0003). The mean duration for the time of passage was 22 ± 2.69 (h ± SD), so future studies using the noninvasive feeding of temperature loggers need to consider that time frame.